Algoritmos utilizados para as quatro operações elementares - Santana, Gracielly da Silva (2016)
This work is meant to study some properties of the four elementary operations on the set of natural numbers. Some relevant aspects to Decimal Numbering System will be verified as well as the expansion of a number on that system. It will also demonstrate the usage of the "Golden Beads", a very useful pedagogical resource when it comes to understanding the Decimal Numbering System and even its usage to solve one of the elementary operations. Therefore, some of the algorithms that can be used to solve each of the four operations: addition, subtraction, multiplication and division.